A longitudinal study of blood folate levels and depressive symptoms among young women in the Southampton Women's Survey. Issue 11 (14th October 2008) - Kendrick, T; Dunn, N; Robinson, S; Oestmann, A; Godfrey, K; Cooper, C; Inskip, H; ,
Abstract : Background: Lower blood folate levels have been associated with depression in cross-sectional surveys, but no studies have examined the relationship prospectively to determine whether the relationship is causal. A follow-up study was designed to examine whether lower blood folate levels predict incident depressive symptoms . Method: Women aged 20–34 years registered in general practices in Southampton, UK, were asked to participate. Baseline assessment included the general health questionnaire (GHQ-12) measure of anxiety and depression, and socioeconomic factors, diet, smoking and alcohol intake. Two years later, participants' general practice (GP) records were examined for evidence of incident symptoms of depression. Results: At baseline, 5051 women completed the GHQ-12 and had red cell folate levels measured, of whom 1588 (31.4%) scored above the threshold for case level symptoms of anxiety and depression on the GHQ-12. Two years later, GP records for 3996 (79.1%) were examined, but 1264 with baseline evidence of depression were excluded from follow-up analysis. Incident depressive symptoms were recorded for 307 (11.2%) of the remaining 2732. Lower red cell folate levels were associated with caseness on the GHQ-12 (adjusted prevalence ratio 0.99 per 100 nmol/l red cell folate, 95% CI 0.98 to 1.00). No relationship was found between red cell folate levels and incident depressive symptoms over 2 years (adjusted hazard ratio 1.00, 95% CI 0.97 to 1.03). Conclusions: Low folate levels were not associated with subsequent depressive symptoms. This suggests that lower blood folate levels may be a consequence rather than a cause of depressive symptoms.